Providing delay guarantees and power saving in IEEE 802.11e network - G. Boggia; P. Camarda; F. Favia; L. Grieco; S. Mascolo (Proceedings of the Third International Conference on Wired/Wireless Internet Communications, 2005)
Recently, the 802.11e Working Group (WG) has proposed the Hybrid Coordination Function (HCF), which has a HCF Controlled Channel Access (HCCA) and an Enhanced Distributed Coordination Access (EDCA), in order to provide QoS in WLANs.In this paper an innovative HCCA-based algorithm, which will be referred to as Power Save Feedback Based Dynamic Scheduler (PS FBDS) providing bounded delays while ensuring energy saving, has been developed. The performance of PS FBDS has been extensively investigated using ns-2 simulations; results show that the proposed algorithm is able to provide a good trade-off between QoS and power saving at both low and high network loads.